The Impact of Investment, Economic Growth, Renewable Energy, Urbanisation, and Tourism on Carbon Emissions: Global Evidence - Kayani, Umar Nawaz; Sadiq, Misbah; Aysan, Ahmet Faruk; Haider, Syed Arslan; Nasim, Ismat (International Journal of Energy Economics and Policy, 2023)
Examining urbanisation and tourism from the perspective of global Sustainable Development Goals is essential for achievinga balance between environmental protection and economic growth in the world’s most polluted nations. Moreover, most polluted countries pay more attention to the nature of foreign direct investment (FDI) inflows to achieve a sustainableenvironment. This study intends to explore the impacts of FDI, tourism, urbanization, and economic growth on carbon dioxide emissions using panel data for the top ten most polluted nations for the period from 2000 to 2019. To guide empirical testing,the panel unit root tests LLC and IPS are used. The outcomes of LLC and IPS advise FM-OLS application on how to accomplish the goals. The findings provide proof of how FDI and other factors affect carbon emissions (CE). Particularly, renewable energy consumption (REC) has a detrimental but minor effect on CE. For the panel of developing nations, FDI had a favourable and significant effect on CE along with economic growth, tourism, and urbanization. The expansion of cities isalso harming nature and ecological footprints. These findings are alarming as all factors cause CE under consideration thatleads to the deterioration of the environment. Therefore, more environmental rules should be put into place to reduce CE, draw in clean FDI, and encourage quality-oriented investment in selected nations. Second, it is important to ensure the deployment of green technology and the upgrading of urbanized structures. The government can take several actions against the use of polluting goods and vehicles in urban areas, and any polluting industries should also be outlawed in such residential areas.